Urban Waterfront Revitalization and Open Space: A case of rezoning waterfront of Yong River in Nanning, China - Luan, Xizhi. (2018)
Abstract: Renovation of public open space on the urban waterfront is a unique part of the urban setting of many waterside cities. Urban waterfront revitalization is not just old city reconstruction and new zone development; it is also a balance between economic needs and the public's demand for access to the water. Waterfront revitalization is a phenomenon in Nanning, China. The Yong River offers main waterfront shorelines in Nanning's core urban area, which covers about 70 kilometers on each bank. The government is gradually emphasizing waterfront open space. A decision to convert undeveloped land, which consists of 50% of total waterfront area, into public space has been made and will result in an increase in public waterfront space from 10% to 20%. This research employs a case study method based on both qualitative and quantitative approaches, utilizing archival research, site observation and survey. The study details the current situation of Nanning's waterfront open space and then makes recommendations for how policy makers and urban planners in Nanning can balance public open space with other land uses in revitalizing their waterfront.; Thesis (M.A.)--Tufts University, 2018.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Penn Lloh.; Committee: Sumeeta Srinivasan.; Keyword: Urban planning.